T Follicular Helper Cell Development and Functionality in Immune Aging - Gustafson, Claire E. (Clin Sci (Lond), 2018)
By 2050, there will be over 1.6 billion adults aged 65 years and older, making age-related diseases and conditions a growing public health concern. One of the leading causes of death in the aging population is pathogenic infections (e.g. influenza, S. pneumoniae). This age-dependent susceptibility to infection has been linked to a reduced ability of the aging immune system to mount protective responses against infectious pathogens, as well as to vaccines against these pathogens. The primary immune response that promotes protection is the production of antibodies by B cells – a response that is directly mediated by T follicular helper (T(FH)) cells within germinal centers in secondary lymphoid tissues. In this review, we will summarize the current knowledge on the development and functionality of T(FH) cells, the use of circulating T(FH) cells as vaccine biomarkers and the influence of age on these processes. Moreover, we will discuss the strategies for overcoming T(FH) cell dysfunction to improve protective antibody responses in the aging human population.